Impact of public expenditure on poverty: role of governance - Ali Madina Dankumo; Suryati Is`Hak; Yusuf Auta; Denthe, Amos (Penerbit Universiti Kebangsaan Malaysia, 2023)
The paper investigated the role of governance in the impacts of government expenditure on poverty. We used a system-Generalised Methods Moments econometric technique with unbalanced panel data of 46 countries in the Sub-Saharan African region covering the period from 1996 to 2019. Good governance plays a vital role in enhancing growth and development, especially, in reducing poverty. The paper ascertains that the problems of governance (corruption and political instability) and public expenditure aggravate poverty. As shown by the results of the marginal effect, governance – corruption and political instability – at both medium and minimum levels aggravates poverty. However, governance is insignificant at the maximum levels. This result suggests that corruption and political instability have a momentous role in mediating the consequences of government expenditure on poverty in the sample countries. Hence, combating corruption and enhancing political stability are crucial obligations of the government for it to witness not only straight progress in its economic performance but also an indirect impacts via poverty reduction.